ETHNOMYCOLOGY STUDIES OF EDIBLE AND MEDICINAL MACROSCOPIC FUNGI IN JEMBER, INDONESIA - Dewi, Rosita Fitrah; Ummah, Nofida Rahmatul; Hidayat, Nurul (Biotik, 2022)
Macroscopic fungi are a critical component of the ecosystem, besides their use in human life. This study aimed to explain edible and medicinal macroscopic fungi in terms of socio-cultural. Ethnomycological studies were uses in holistically analysis between mycology and social science. Specimen collection and interviews were conducted using purposive sampling in 5 sampling stations in Jember to determine the diversity of macroscopic fungi and their cultural significance. Quantitative approaches were used to determine Use values (UV). This study found nineteen edible and medicinal macroscopic fungi included in Basidiomycota and Ascomycota. The highest UV was obtained by P. ostreatus and Termitomyces spp. used for food. Information about macroscopic fungi was obtained from oral history.